(untitled) (Journal of Environment Sciences, 2025)
Biological invasions are increasingly recognized as significant drivers of economic and environmental harm, largely due to their negative impacts on biodiversity and ecosystem processes. Understanding and quantifying the effects of Invasive Plant Species (IPS) on agricultural land has therefore become a key research priority to inform effective policy and management strategies. In this study, I surveyed agricultural land in Mangalpur village, Chandrapur Municipality-01, Rautahat district, Nepal, to assess the structural (physical) attributes of IPS and conducted a socio-economic survey to evaluate their impacts. Thirty 1×1 m² plots were established, and eight IPS belonging to four plant families were identified through cluster analysis. Key metrics such as density, frequency, abundance, cover, Relative Population Density (RPD), Relative Frequency (RF), Relative Abundance (RA), and Relative Cover (RC) were measured. Additionally, species richness, species diversity, and Importance Value Index (IVI) were calculated. The results revealed that three species Ageratum conyzoides, Argemone mexicana, and Erigeron karvinskianus were the most dominant IPS, with Ageratum conyzoides exhibiting the highest density. While local farmers are aware of the IPS problem, management practices such as manual removal, burning, chemical application, and ploughing are only occasionally implemented. This highlights an urgent need for more systematic and effective control measures, as the current level of invasion suggests the situation could worsen in the future if left unaddressed.